3-Hydroxy-2-[(4-hydroxybenzyl)azaniumyl]propanoate monohydrate - Min Gao (IUCrData, 2017)
In the title hydrated zwitterion, C10H13NO4·H2O, the N—C—C—OH side chain shows a gauche conformation [torsion angle = −59.05 (18)°]. In the crystal, the components are linked by O—H...O, N—H...O and C—H...O hydrogen bonds to generate a three-dimensional supramolecular network.